Methanol as a Main Fuel to Replace Gasoline Without Global Warming - Bockris, John O’M. (Journal of Technology Innovations in Renewable Energy, 2013)
The world temperature will increase by approximately 8OC by 2100. This would bring the temperature in parts of the Middle East to values causing heat stroke and death. Methanol made from pure H2 and CO2 removed from the atmosphere would cause no global warming and could be made from inexhaustible compounds on the surface of the earth. Cheaper ways of making this fuel may be available.